PEMBELAJARAN ALAT MUSIK KEYBOARD BAGI ANAK TUNADAKSA DI SANGGAR MUSIK GITA LOKA GRESIK - Novanicha, Putri (Jurnal Pendidikan Sendratasik, 2024)
Learning the art of music is given to children with physical disabilities to explore their potential and provide new experiences and can help children with special needs improve concentration and skills, self-confidence, train to work well together, and as a medium for self-expression. This study aims to: (1) describe the process of learning keyboard instruments for children with disabilities in the Gita Loka Gresik Music Studio, (2) describe the learning outcomes of keyboard instruments for children with disabilities in the Gita Loka Gresik Music Studio. The object of research is learning the art of keyboard music for children with physical disabilities at the Gita Loka Gresik Music Studio. This research method uses a qualitative approach. Data collection techniques include interviews, observation, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Data validity uses technical triangulation and source triangulation. The purpose of learning the art of music using a keyboard instrument is to train the motor nerve abilities of disabled children's hands, be able to read number notes and be able to play songs. The results obtained: (1) the learning process of keyboard musical instruments that is applied to children with disabilities is able to increase motor movements in the fingers, (2) the material used is not entirely centered on children with disabilities, (3) the method used is the lecture method, demonstrations, and exercises/drills, (4) the results of the pre-test and post-test showed the development of motor sensory stimuli and skills in playing keyboard instruments. Keywords: Learning, Music Arts, Keyboard, Children with Physical Impairment